Customer Satisfaction In Banking Industry Of Melaka - Peng, Ngo Siau (2002)
Base on the five-critical factor of customer -perceived service quality and four-dimension of relationship marketing, this study is to identify the key determinant of service quality and relationship marketing in banking services.